Personality traits: Support for survive in pandemic Covid-19 for SMEs - Mega Dwi Septivani; Alivia Meyrizka Utami (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – Small and Medium Enterprises (SMEs) play an important role in the Indonesian economy. However, the Covid-19 pandemic has hampered the economic sector, companies must be able to create the best market opportunities one way through which entrepreneurial personality traits and skills can influence the market and entrepreneurial orientation. Therefore, it is important to know the important role of the personality and skills of SME owners in responding to this situation. Based on this, this study aims to examine the relationship between personality traits, entrepreneurial orientation, market orientation and performance.Methodology – This study uses a survey with a structured questionnaire with a total of 103 SMEs owners in Indonesia.Findings – This study shows that the ability to negotiation skill and risk taking has a significant effect on both entrepreneurial orientation and market orientation, but optimism and locus of control have no effect on market orientation and orientation.Implications – This study promises to examine how the positive role of personality traits here can help managers view any crisis in a new perspective. As for the managerial implications a manager can use the influence of their personality to inspire and mobilize their team to work effectively to achieve common goals.Originality – This research is to provide a useful view for SMEs owners, it is important to be entrepreneurship and market oriented in order to improve SMEs performance and increase awareness of the importance and adopting new technology as an effort to deal with the Covid-19 and anticipate the economy in the future.